Clinical impact of genetic aberrations in gastric MALT lymphoma: a comprehensive analysis using interphase fluorescence in situ hybridisation. - Nakamura, S; Ye, H; Bacon, C; Goatly, A; Liu, H; Banham, A; Ventura, R; Matsumoto, T; Iida, M; Ohji, Y; Yao, T; Tsuneyoshi, M; et al. (2007)
BACKGROUND AND AIMS: There is a need for genetic biomarkers to guide prognosis and management of gastric mucosa-associated lymphoid tissue (MALT) lymphomas. We assessed the incidence and clinical significance of the MALT lymphoma-associated genetic abnormalities t(11;18)/API2-MALT1, t(1;14)/BCL10-IGH, t(14;18)/IGH-MALT1, t(3;14)/FOXP1-IGH, and extra copies of MALT1 and FOXP1 in gastric MALT lymphomas from Japan. METHODS: The presence of translocations and copy number changes involving MALT1, IGH and FOXP1 were assessed in 90 cases of gastric MALT lymphoma using interphase fluorescence in situ hybridisation (FISH). In cases carrying a MALT1 translocation, FISH for API2-MALT1 was performed, whereas in those carrying an IGH translocation, FISH was performed for BCL10, BCL6, BCL2, c-MYC and/or CCND1. RESULTS: t(11;18)/API2-MALT1 was detected in 18 of 87 (21%) cases and was significantly associated with Helicobacter pylori-negativity, resistance to H pylori eradication and Bcl10 nuclear expression. Four of 68 (6%) cases carried a translocation involving IGH and FOXP1 (n = 1), BCL2 (n = 1) or an unknown partner (n = 2). Neither t(1;14)/BCL10-IGH nor t(14;18)/IGH-MALT1 was detected. Extra copies of MALT1 and FOXP1 were detected in 18 of 71 (25%) cases and 10 of 59 (17%) cases, respectively. The presence of extra copies of MALT1 was significantly associated with progression or relapse of lymphoma, and was an independent adverse prognostic factor for event-free survival as determined by multivariate analysis. CONCLUSIONS: t(11;18)/API2-MALT1 is frequent, whereas IGH-involved translocations are rare in gastric MALT lymphoma in Japan. The presence of extra copies of MALT1, often suggestive of partial or complete trisomy 18, is a frequent genetic aberration in gastric MALT lymphoma, which appears to predict adverse clinical behaviour.